The relationship between sugar-sweetened beverages, sleep disorders, and diabesity - Zhang, Yi; Liu, Chao; Xu, Yijing; Wang, Yanlei; Zhang, Yulin; Jiang, Tian; Zhang, Qiu; , the China National Diabetic Chronic Complications Study Group (Frontiers in Endocrinology, 2023)
Background: Diabetes and obesity in adults are global issues. Obesity and type 2 diabetes mellitus (T2DM) are increasingly categorized under the umbrella term “diabesity.” Health risk factors (HRFs), which include altering sleep habits and reducing sugar-sweetened beverages (SSBs) consumption, have emerged as relatively novel and crucial strategies for preventing and treating diabetes. Objective: We aimed to explore: 1) whether SSBs could affect diabesity in China’s community; 2) whether HRFs could moderate this relationship; and 3) whether a three-way interaction exists between HRFs, SSBs, and diabesity. Methods: On December 10, 2018, we investigated diabetes complications in four cities in Anhui Province and obtained basic and lifestyle information using a detailed questionnaire. The primary exposure was SSBs and outcomes were body mass index (BMI) and waist circumference (WC), while glycated hemoglobin (HbA1c) and sleep patterns (including duration and disorders) were considered moderators. Results: Overall, 1920 participants were enrolled, and those who did not complete the questionnaire were excluded. Finally, this study included 1765 participants, with a response rate of 92.0%. The mean age was (57.10 ± 10.0) years. Patients with lower educational levels were more likely to have a lower prevalence of WC (χ2 = 2.73) and BMI (χ2 = 3.47), and some HRFs were positively correlated with WC and BMI. Additionally, SSBs were significantly associated with BMI (β = 1.29) and WC (β = 2.97), and there was also differences based on sex, some HRFs, such as HbA1c, FBG and TG, showed higher levels in male participants, whereas TC level was higher in female participants. In the moderation analysis, sleep patterns were also associated with total cholesterol, triglyceride, and BMI. Furthermore, there were three-way interaction effects among HbA1c, sleep patterns, and SSBs on total cholesterol, triglyceride, BMI, and WC. Moreover, sensitivity analysis demonstrated that our results were robust. Conclusion: SSBs positively correlated with patterns dose-dependently. Moreover, SSBs could also be associated with sleep patterns, and blood glucose levels were correlated with diabesity. A three-way interaction effect was discovered between SSBs, sleep patterns, HbA1c levels, and patterns. Therefore, understanding the diabesity caused by SSBs and other HRFs can help prevent its occurrence.